An Integrated Model of Service Experience, Emotions, Satisfaction, and Price Acceptance: An Empirical Analysis in the Chinese Hospitality Industry - Ali, Faizan; Amin, Muslim; Cobanoglu, Cihan (Journal of hospitality marketing & management, 2016)
This study investigated the relationships between service experience, emotions, satisfaction, and price acceptance in Chinese resort hotels. A self-administered survey was used to collect the data from respondents. A total of 500 questionnaires were distributed to customers at resort hotels in three cities of China; 170 were returned representing a response rate of 34%. The results of this study show a significant relationship between service experience and emotions, jointly influencing customer satisfaction, which influences price acceptance of customers. These results indicate that management of resort hotels need to consider how the physical environment, interaction with employees, and other customers within resort hotels can be managed in order to satisfy the customers emotionally, which will lead them to accept premium prices charged by resort hotels. This study would enable resort hotels to have a better understanding of how a great experience and positive emotions influences customer satisfaction and price acceptance.